2019
DOI: 10.1108/bpmj-03-2019-0127
|View full text |Cite
|
Sign up to set email alerts
|

Improving the financial performance of SMEs

Abstract: Purpose The purpose of this paper is to assess the influence of the presence in foreign markets on small- and medium-sized enterprises’ (SMEs) financial performance. Furthermore, it seeks to examine the moderating effect of corporate group and alliance portfolio size on this relationship. Design/methodology/approach First, the authors develop hypotheses concerning the relationship between the presence in foreign markets and SMEs’ financial performance as well as the moderating role of the size of an SME’s co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 86 publications
0
6
0
Order By: Relevance
“…Hence, an ICT strategy could be a mediating factor in determining profitability between the agricultural and the non-agricultural sectors when the results in Panel A are compared with Panel B. Therefore, the agricultural industry in this study lacks the resources and capabilities to harness digital technology to their advantage and may need to secure agreements and cooperative efforts with other SMEs external to the industry to create value for the economy (Ardito et al, 2019;Capaldo & Petruzzelli, 2011;Ceipek et al, 2020;Correani et al, 2020;Elia et al, 2019;Petruzzelli, 2019). In Panel C, the aggregated results indicate that an enterprise having ICT strategy depends on the industry to a significant extent.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, an ICT strategy could be a mediating factor in determining profitability between the agricultural and the non-agricultural sectors when the results in Panel A are compared with Panel B. Therefore, the agricultural industry in this study lacks the resources and capabilities to harness digital technology to their advantage and may need to secure agreements and cooperative efforts with other SMEs external to the industry to create value for the economy (Ardito et al, 2019;Capaldo & Petruzzelli, 2011;Ceipek et al, 2020;Correani et al, 2020;Elia et al, 2019;Petruzzelli, 2019). In Panel C, the aggregated results indicate that an enterprise having ICT strategy depends on the industry to a significant extent.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, Welsch, Price, and Stoica (2013) concluded that entrepreneurs share similar sets of values, regardless of culture. Regardless of the differences and/or similarities among entrepreneurs, however, firms sometimes engage in alliances in an attempt to complement their innovation capabilities although such alliances may be exploitative instead of being explorative and may not have a positive effect on the financial performance of the SME (Ardito, Galati, Messeni Petruzzelli, & Corvino, 2019;Capaldo & Petruzzelli, 2011;Elia, Petruzzelli, & Piscitello, 2019;Petruzzelli, 2019). Saunila (2014) adopted a linear regression model to analyse the innovation capability of SMEs and their perceived performance and had four key findings.…”
Section: Innovation and Firm Performancementioning
confidence: 99%
“…Particular emphasis should be put on those companies that have never been involved in collaboration activities, as current policy measures tend to support companies that have already experienced cooperation. Second, policy measures should consider OI efficiency, particularly for SMEs, with a particular focus on the diminishing returns of OI in relation to innovation performance (Greco et al, 2017;Ardito et al, 2019). Such a process may challenge the usefulness of establishing several and merely formal collaborations aimed at matching the constraints requested by public authorities, which can be ineffective in terms of innovation performance in that funds are dispersed.…”
Section: Policy Implicationsmentioning
confidence: 99%
“…Thus, the capacity variable of hospital partners was defined as the ratio of the top five hospitals to the total number of participant hospitals in government‐funded R&D projects. Meanwhile, the socially dominant partner portfolio size was measured by the absolute number of participant hospitals (Ardito et al, 2020). It is worth noting that we counted it as one even when a hospital was involved in multiple R&D projects in the same year.…”
Section: Methodsmentioning
confidence: 99%
“…Firms form inter‐organisational relationships with multiple partners through various joint projects to retain complementarity and increase knowledge transfer based on their partner portfolios (Ardito et al, 2020; Kale & Singh, 2009; Laursen & Salter, 2006). A similar reasoning can be applied to inter‐organisational relationships with socially dominant partners.…”
Section: Hypotheses Developmentmentioning
confidence: 99%